Pengembangan Web Scraper Menggunakan Algoritma DFS Untuk Analisis Penyusupan Situs Judi Online Pada Domain AC.ID, GO.ID, MY.ID, .ID, Dan SCH.ID - Ramadhan, Angga Rizki; Dasuki, Moh.; Muharom, Lutfi Ali (Computer Science and Information Technology, 2026)
The infiltration of online gambling into official domains such as ac.id, go.id, my.id, .id, and sch.id has become a serious issue because it can damage institutional reputation, disrupt information security, and reduce public trust. One of the common objectives of this infiltration practice is to boost the SEO ranking of the gambling sites by exploiting the authority of official domains. This research aims to develop a web scraper using the Depth First Search DFS algorithm capable of performing deep traversal on website structures and automatically analyzing the infiltration of online gambling links. The system conducts crawling, extraction of html elements containing gambling-related links, text analysis, and keyword pattern matching. Testing was carried out in several stages, starting with an initial evaluation on 40 domains followed by a formal accuracy test on 50 domains. The results show that the system performs stably and consistently when conducting traversal using DFS. The achieved accuracy reached 98%, with 49 correct analyses and 1 detection error. Further evaluation on an additional 60 domains increased the accuracy to 98,33% after improvements were applied to the analysis module.